The impact of cumulative pressure on accounting students' propensity to commit plagiarism: an experimental approach - Koh, H.; Scully, Glennda; Woodliff, D. (Wiley-Blackwell Publishing Asia, 2011)
Adopting aspects of Jones, T.M., 1991, Academy of Management Review 16, 366-395 issue-contingent model of ethical decision-making to guide our choice of variables, we investigate perceptions of factors that affect student plagiarism. In an experimental setting, time pressure and assessment weighting are manipulated between-subjects, whilst the severity of plagiarism is examined within-subjects. Our findings confirm that time pressure and assessment weighting are positively related to perceptions of the likelihood of plagiarism and that plagiarism is perceived as more likely for less severe acts. Further, the likelihood of plagiarism increases as the cumulative pressure of both time deadline and assessment weighting increases.